3D biomechanical analysis of targeted and non-targeted drag flick shooting technique in field hockey - Gülbin Eskiyecek, C.; Meriç Bingül, B.; Bulgan, C.; Aydin, M. (Acta Kinesiologica, 2018)
The aim of this study was tocompare targeted and non-targeted drag flick field hockey shooting techniques in the penalty corner area, using a three-dimensional kinematic analysis. Eleven male field hockey players playing in the super league(mean age:19,82±1,40years) participatedvoluntarily. Seven high-speed cameras (Oqus 7+)with 120Hz refresh rates were used. Field calibration was completed via the wand method. The data wereevaluated in two phases: start and finish.Players undertook three drag flick shots to the box using targeted and non-targeted techniques. The angular kinematics and stroke force applied to the stick were analyzed using the Qualisys Track Manager Program V2.12, and ball velocity statistics were gathered with the SPSS 18.0 program. To comparebetween the targeted and non-targeted shots of the drag flick shooting techniques, t-test was applied. At the drag flick of the players, significant differences were noticed at the angular speed of the right shoulder and the left knee, and the angular acceleration of the right hip in the starting phase, and also at the right hip angular acceleration atthe finish phase. When the ball speed data considered, a significant decrease was observed between the targeted and non-targeted drag flick shots. Significant correlation was found out between some variables, at the angular kinematics and both force applied on the stick and the ball speed values (p=0.05). In conclusion, to make an accurate target shot the players maximize their targeted shooting rates, particularly by decreasing the speed of their lower extremities.